Complete genome sequence of the lytic Pseudomonas fluorescens phage ϕIBB-PF7A - Sillankorva, Sanna (2011)
Background Phage ϕIBB-PF7A is a T7-like bacteriophage capable of infecting several Pseudomonas fluorescens dairy isolates and is extremely efficient in lysing this bacterium even when growing in biofilms attached to surfaces. This work describes the complete genome sequence of this phage. Results The genome consists of a linear double-stranded DNA of 40,973 bp, with 985 bp long direct terminal repeats and a GC content of approximately 56%. There are 52 open reading frames which occupy 94.6% of the genome ranging from 137 to 3995 nucleotides. Twenty eight (46.7%) of the proteins encoded by this virus exhibit sequence similarity to coliphage T7 proteins while 34 (81.0%) are similar to proteins of Pseudomonas phage gh-1. Conclusions That this phage is closely related to Pseudomonas putida phage gh-1 and coliphage T7 places it in the "T7-like viruses" genus of the subfamily Autographivirinae within the family Podoviridae. Compared to the genome of gh-1, the sequence of ϕIBB-PF7A is longer and contains more genes with unassigned function and lacks a few potentially essential and non-essential T7 genes, such as gene1.1, 3.8, and 7.